Safeguarding Australia's Community Heritage Sector: A Consideration of the Institutional Wellbeing of Volunteer-Managed Galleries, Libraries, Archives, Museums and Historical Societies. - Baker, Sarah; Cantillon, Zelmarie (Australian Historical Studies, 2020)
In Australia, the community heritage sector – galleries, libraries, archives, museums and historical societies managed by volunteers – plays a significant role in recording and preserving the diversity of Australia's cultural heritage. However, these community heritage organisations face uncertain futures. This article offers four examples of heritage organisations located in New South Wales, Queensland and South Australia which have struggled with organisational sustainability arising from various financial, human, physical, skills, and expertise challenges. We assess some of the common problems threatening the longevity of community heritage organisations and what action is needed to safeguard this sector into the future.